Effect of Water Vapor on the Reduction Kinetics of Hematite Powder by Hydrogen-Water Vapor in Different Stages - Mao, Xudong; Hu, Xiaojun; Fan, Yuewen; Chou, Kuochih (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
The powder of hematite sample was isothermally reduced with hydrogen-water vapor gas mixture at 1023K-1273K. The results indicated that the overall reduction process of hematite could be separated into three stages (Fe2O3-Fe3O4-FeO-Fe) that proceed in series to study. As the reaction proceeded, the water vapor had an increasing influence on the reaction rate. The average reaction rate dropped by 53.6% in the stage 1 when the water vapor content of gas reactant rose from 0% to 50% at 1023K, and it decreased by about 77.2% in the stage 2. However, in the stage 3, when the water vapor content only increased from 0% to 20%, it decreased by about 78.1%. Besides, the average reaction rate had a roughly negative linear relationship with the water vapor content, and the results further shown that the effect of water vapor on the reduction reaction increased with increasing reaction temperature at all stages of the reduction reaction. The microstructure of reduction products showed that it still had some holes, which the channel for hydrogen diffusion was not seriously blocked. In order to further clarify the influence of water vapor in the reduction stage, different models were considered, and the range of apparent activation energy of different stages obtained by model fitting was about 20-70 kJ/mol, which also confirmed the absence of solid-state diffusion phenomenon.
Keywords: reduction; water; hydrogen; kinetics mechanism